Dual-Sink: Using Mobile and Static Sinks for Lifetime Improvement in Wireless Sensor Networks - Xiaobing Wu; Guihai Chen (2007 16th International Conference on Computer Communications and Networks, 2007)
Mobile sink has been adopted by many schemes for lifetime improvement in wireless sensor networks. It is necessary to propagate the topological or location changes caused by the sink movement across the network for successful data delivery. However, previous studies on using mobile sink either assume that some global information of the network is already available or let the mobile sink convey the global information through repeated network-wide broadcasting. As a result, the gains in network lifetime from sink mobility can be offset by the broadcasting which incurs extra high energy loss. To address this problem, we propose dual-sink, an energy-efficient and distributed protocol for data collection in wireless sensor networks. Both a mobile sink and a static sink are used by Dual-Sink. The mobile sink only needs to broadcast its location to a subset of nodes in the network each time when it stops. Simulation results show that when it scales up, the network using Dual-Sink enjoys steady lifetime improvement from sink mobility, whereas the network with only one mobile sink performs no better than the network with a single static sink.